EventSegNet: Direct Sparse Semantic Segmentation from Event Data - Pengju Li; Yuqiang Fang; Jiayu Qiu; Jun He; Jishun Li; Qinyu Zhu; Xia Wang; Yasheng Zhang (Remote Sensing, 2024)
Semantic segmentation tasks encompass various applications, such as autonomous driving, medical imaging, and robotics. Achieving accurate semantic information retrieval under conditions of high dynamic range and rapid scene changes remains a significant challenge for image-based algorithms. This challenge is primarily attributable to the limitations of conventional image sensors, which can experience motion blur or exposure artifacts. In contrast, event-based vision sensors, which asynchronously report changes in pixel intensity, offer a compelling solution by acquiring visual information at the same rate as the scene dynamics, thereby mitigating these limitations. However, we encounter a significant challenge in event-based semantic segmentation tasks: the need to expend time on converting event data into frame images to align with existing image-based semantic segmentation techniques. This approach squanders the inherently high temporal resolution of event data, compromising the accuracy and real-time performance of semantic segmentation tasks. To address these issues, this work explores a sparse semantic segmentation approach that directly addresses event data. We propose a network named EventSegNet that improves the ability to extract geometric features from event data by combining geometric feature enhancement operations and attention mechanisms. Based on this, we propose a large-scale event-based semantic segmentation dataset that provides labels for each event. Our approach achieved a new F1 score of 84.2% on the dataset. In addition, a lightweight and edge-oriented AI inference deployment technique was implemented for the network model. Compared to the baseline model, the optimized network model reduces the F1 score by 1.1% but is more than twice as fast computationally, enabling real-time inference on the NVIDIA AGX Xavier.